Villages cinemas (Summa+, 1999)
V.C. Avellandea, arq. Alvariñas-Bodas-Miani; V.C. Pilar, arq. Bodas.Miani-Anger, 1997; Hoyts Cinemas Abasto, arq. Antonini, Schon..; V.C. Recoleta, arq. Bodas-Miani-Anger, 1999